PENGARUH TINGKAT SATUAN PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT BANK RIAU KEPRI KANTOR PUSAT PEKANBARU - Husna, Anti Miratul Husna Miratul; ', Suarman Suarman; ', Ngadlan Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was conducted to examine the effect of Education and Training for Employee Performance. The population used in this study there are 182 permanent employees working in Bank Riau Kepri headquarters Pekanbaru, the sample in this study were 57 employees, type of data used is qualitative data. Data analysis technique using multiple linear analysis, t test and f test with significance level of 0.05%.The result showed that the Education and training simultaneously affect the Employee Performance. Based on the partial results of the study showed Education of positive and significant effect on the Employee Performance, meanwhile Training significant negative effect on the Employee Performance. The coefficient of determination shows that the Education and Training Care Employee Performance affect 21,5% and the remaining 78,5% are not described in this research model.Keywords : Education, Training and Employee Performance